Priming of reovirus transcription by GppppG and formation of CpG(5')GpC. - Yamakawa, M (1982)
Compounds of general structure N(5')pn(5')N were used by the reovirus-associated RNA polymerase as primers for template-directed synthesis of virus-specific oligonucleotides and RNA. Structural requirements for activity included a guanosine residue and at least four phosphates--i.e., G(5')pppp(5')N. Gp4G incubated with viral cores in the presence of CTP yielded Gp4GpC and CpGp4GpC. In a complete transcription mixture, Gp4G was also incorporated into the 5' termini of full-length transcripts in the unmethylated forms Gp4GpC and CpGp4GpC, in contrast to viral mRNAs that contain 5'-terminal m7GpppGmpC formed de novo. Gp5G, Gp6G, and Gp4A but not Gp2G, Gp3G, and Ap4A also primed reovirus transcription and inhibited RNA methylation.